The effect of compensation, career development and job satisfaction on employee turnover intention at hooray school Bali - Ni Made Elita Ambara Putri; Putu Kepramareni; I Gst. Ngurah Bagus Gunadi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study aims to identify the influence of compensation, career development, and job satisfaction on employee exit intention at Hooray School Bali, as well as explore the mediating role of job satisfaction in the relationship. This research uses quantitative methods with Partial Least Squares (PLS) based Structural Equation Modeling (SEM) analysis. The research sample consisted of 36 teachers and employees of Hooray School, who were selected using total sampling technique. Data were collected through questionnaires and analyzed using SmartPLS. The hypotheses tested include the effect of compensation and career development on turnover intention, as well as the mediating role of job satisfaction. The results showed that compensation had no significant effect on turnover intention, career development also had no significant effect on turnover intention, and job satisfaction did not mediate the relationship between these two variables and turnover intention. However, compensation and career development have a significant positive effect on job satisfaction. The limitations of this study lie in the small sample size and limited location coverage. This study contributes to human resource management, especially in the context of reducing turnover intention through improving career development and job satisfaction in educational institutions.